Problem samobójstw w perspektywie psychiatrycznej i psychologicznej - Raniszewska-Wyrwa, Agnieszka (Acta Universitatis Lodziensis. Folia Psychologica, 2010)
Suicide is a type of behaviour which assumes the need of overcoming the instinct of self-preservation, as well as overcoming the natural fear of death; it is therefore an act which is in contradiction with basic human instincts. Scientists looking for the answer to the question, what makes people decide that they want to end their life, focus on different aspects of the problem, and as a consequence it is possible to distinguish several directions of suicidal behaviour analysis; they include, among others, psychiatric and psychological directions. Psychiatry analyses suicide in the context of psychological disorders of a person. Psychology studies self-destructive behaviours with particular focus on human psychology, motivation, personality and consciousness of the made decision. Findings of those sciences will be the subject of this article.